Positive stock information in out-of-the-money option prices - Konstantinos Gkionis; Alexandros Kostakis; George Skiadopoulos; Przemyslaw S. Stilger (Queen Mary University of London, School of Economics and Finance, 2018)
We examine whether the option market leads the stock market with respect to positive in addition to negative price discovery. We document that out-of-themoney (OTM) option prices, which determine the Risk-Neutral Skewness (RNS) of the underlying stock return's distribution, can embed positive information regarding the underlying stock. A long-only portfolio of stocks with the highest RNS values yields significant positive alpha in the post-ranking week during the period 1996-2014. This outperformance is mainly driven by stocks that are relatively underpriced but are also exposed to greater downside risk. These findings are consistent with a trading mechanism where investors choose to exploit perceived stock underpricing via OTM options due to their embedded leverage, rather than directly buying the underlying stock to avoid exposure to its potential downside. Due to the absence of severe limits-to-arbitrage for the long-side, the price correction signalled by RNS is very quick, typically overnight.
Keywords: G12; G13; G14; 330; Option-Implied Information; Price Discovery; Risk-Neutral Skewness; Stock Underpricing; Downside Risk